APROVECHAMIENTO DE RECURSOS TIC PARA MEJORAR EL APRENDIZAJE DE LOS LENGUAJES DE LAS CIENCIAS: INVESTIGACIONES DIDÁCTICAS EN EL AULA - Gras-Martí, Albert (2005)
We have investigated about learning improvements derived from the use of modeling tools based on the information and communication technologies (ICT). In this paper we will show how its implementation turned out, obtaining experimental data using sen-sors and videos, simulations and spreadsheets. Detailed studies of the student’s answers have been made, before and after the use of the respective tool, as well as comparisons between the results of several courses. The conclusions of our investigations encourage the use of this tools that facilitates the understanding of science’s different languages as: iconic language, algebraic, tabular, formal, etc.